Intentionally Changing Everything: Deliberate Constructing in Corruption Case - Kamsi, Kamsi; Julianto, Very; Billah, Mu'tashim; Karimullah, Suud Sarim (Universitas Negeri Semarang, 2023)
Handling corruption cases is not always consistent in emphasizing the element of intention/intentionally. Theoretically, the concept of deliberation has been put forward by some experts. However, in the realm of implementation the theoretical studies of those experts become contradictory. This is because there is no certainty of indicators of intent. Deliberation in this research is viewed from criminal law and psychology. The method used in this research is Forum Group Discussion (FGD). Then also is performed professional judgment by legal practitioners and academics. The results show that law enforcers have a common perception in viewing the deliberate in cases of corruption. Law enforcers in understanding the Articles use the theory of science and the theory of Possibility in Certainty. It is deliberate behavior when viewed from psychology produces a construct that can be measured using the science theory.